2019
DOI: 10.18805/ajdfr.dr-128
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes and other Listeria species in raw milk and sausage in East Algeria

Abstract: Listeria monocytogenes is a pathogenic bacterium that can cause Listeriosis in humans. The aim of this study is to isolate and enumerate L. monocytogenes and other Listeria species from raw milk and sausage samples collected in East Algeria. A total of 87 food samples were analyzed according to ISO 11290-1 and ISO 11290-2 methods. Of the samples examined, 10.34% were found to be positive for Listeria spp. Three species of Listeria were detected, in which L. innocua was the most commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…A high level of total flora count (9.38 × 10 5 CFU ml -1 ) detected in raw milk before treatment indicating a very poor quality compared to the accepted standards (10 5 CFU ml -1 ) (OJAR, 1998). However, these data are consistent with the Benhalima et al (2019). After pasteurization, thermofilic flora count of raw milk ranged between 2.4 × 10 4 to 29.4 × 10 4 CFU ml -1 with an average of 5.62 × 10 4 ± 13 × 10 5 CFU ml -1 considered as higher than the limit of 3 × 10 4 CFU ml -1 (OJAR, 1998).…”
Section: Effect Of Heat-treatment On the Milk Bacteriological Qualitiessupporting
confidence: 73%
“…A high level of total flora count (9.38 × 10 5 CFU ml -1 ) detected in raw milk before treatment indicating a very poor quality compared to the accepted standards (10 5 CFU ml -1 ) (OJAR, 1998). However, these data are consistent with the Benhalima et al (2019). After pasteurization, thermofilic flora count of raw milk ranged between 2.4 × 10 4 to 29.4 × 10 4 CFU ml -1 with an average of 5.62 × 10 4 ± 13 × 10 5 CFU ml -1 considered as higher than the limit of 3 × 10 4 CFU ml -1 (OJAR, 1998).…”
Section: Effect Of Heat-treatment On the Milk Bacteriological Qualitiessupporting
confidence: 73%
“…Throughout the world, national mastitis control programs are formed in many countries. Within the frame of these programs, the applications on barn and environment planning, milking management and hygiene, the maintenance and cleaning of milking equipment, teat cleaning and applying antiseptic (teat dipping) on teats before and after milking, monitoring the udders of dairy cows in terms of clinical and subclinical mastitis infections in farms, and dry period management are determined as the standards (6,10).…”
Section: Discussionmentioning
confidence: 99%
“…L. monocytogenes causes encephalitis, abortion, septicemia, ocular form and mastitis infections in cows (27). Also, L. monocytogenes is an opportunistic pathogen and causes especially important food-borne infections in human beings as well as the infections it causes in animals (10). Particularly elderly people, pregnant women, newborns and the people with a suppressed immune system are quite susceptible to these infections (25,36).…”
Section: Introductionmentioning
confidence: 99%
“…They found that 4% of minced meat, beef burger, and luncheon samples were infected with L. monocytogenes. In a survey conducted by Benhalima et al (2019) over a 10-year period in China, RTE meats and raw meats were contaminated with L. monocytogenes 3.2 and 8.5%, respectively, and meat products from northeastern and central China had the highest occurrence of L. monocytogenes. In East Algeria, the prevalence of L. monocytogenes in sausage was 33.3% (Liu et al, 2020).…”
Section: Listeria Monocytogenes and Its Presence In Meat Productsmentioning
confidence: 99%